Macunaima 88 : Pintura - Escultura - Objeto - Instalação. (Rio de Janeiro : FUNARTE/Fundação Nacional de Arte, 1988)
Marzano, Angelo ; Guagliardi, Carla ; Bevilácqua, Carlos ; Euvaldo, Célia ; Frota, Eduardo ; Tedesco, Elaine ; Miguez, Fábio ; Gomes, Fernanda ; Cassaro, Franklin ; Fidelis, Gaudêncio ; Machado, José Carlos ; Vieira, José Mauricio ; Vinci, Laura ; Menna Bareto, Lia ; Volpini, Lincoln ; Geisel, Lorena ; Koch, Lúcia ; Giannotti, Marco ; Chaves, Marcos ; Coelho Benjamim, Marcos ; Palhano, José ; Monteiro, Paulo ; Pasta, Paulo ; Magalhães, Rachel ; Michelin, Simone
Macunaima 88 : Pintura - Escultura - Objeto - Instalação, Rio de Janeiro, 1988
Portugees
kunstcatalogus